Tratamento anaeróbio-aeróbio de águas residuárias do processamento de cafeeiro em reatores biológicos - Villa Montoya, Alejandra Carolina [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Coffee processing wastewater (CPWW) is an important organic waste with high pollution potential. Anaerobic digestion in two-stages combined with post-treatment with aerobic phase, can enable the production of by-products with added value. In this study we evaluated the combination of two-stage UASB reactors (R1 and R2) followed by Sequencial Batch Reactor (SBR), for the stabilized effluent and methane production, with and without phosphorus supplementation. We applied gradual increase of organic loading rate (OLR) from 0,5 to 6 g CODtotal (L d)-1, with hydraulic retention times (HRT) of 60, 30 and 24 h in R1, R2 and SBR, respectively. The affluent COD was increased from 6974 to 14939 mg L-1 O2, thus decreased of removals from 87% to 80%, while phosphorus supplementation had no significant effect on the organic matter removal. Although, the nutritional correction improved effluent quality, increasing the phenol removal efficiencies from 70% to 94% with phosphorus addition, however did not induce differences in the biogas production. The highest methane production occurred in R1 and were 0,29 and 0,74 L CH4 (L d)-1 in the different tests. Additionally, the anaerobic - aerobic system removed from 40% to 71% of the total Kjeldahl nitrogen (TKN) and total phosphorus (TP) without affluent nutritional correction, and from 41 to 81% of TKN and TP when the affluent was corrected. Similarly, obtained inorganic elements removal such as Fe, Zn, Cu, Mn, Mg, Ca and K, especially during anaerobic digestion. The R2 showed low performance both for the production of bioenergy as to improve the quality of the effluent, although helped to stabilize the load shocks and toxic compounds such as phenols before changes in physical and chemical characteristics of CPWW. In the RBS were observed nitrification and biological phosphorus removal phenomena, although it decreased the aerobic reaction time and will add one anoxic reaction cycle. UASB system showed an ...

As águas residuárias do processamento de frutos de cafeeiro por via úmida (ARC) constituem-se num importante resíduo orgânico com grande potencial poluente. A digestão anaeróbia em dois estágios combinado com o pós-tratamento aeróbio, possibilita a produção de subprodutos com valor agregado. Neste trabalho foi avaliada a combinação de dois reatores UASB em série (R1 e R2) seguidos de um reator em batelada sequencial (RBS), para a produção de metano e efluente estabilizado com e sem suplementação de fósforo. Foi aplicado o aumento gradual de cargas orgânicas volumétricas (COV) de 0,5 a 6 g DQOtotal (L d)-1, com tempos de detenção hidráulica de 60, 30 e 24 h no R1, R2 e RBS, respectivamente. A demanda química de oxigênio (DQO) dos afluentes aumentou de 6974 para 14939 mg L-1 O2, com isto, as remoções diminuíram de 87% para 80%, e a suplementação de fósforo não teve um efeito significativo sobre a remoção da matéria orgânica. A correção nutricional permitiu melhorar a qualidade dos efluentes, aumentando as eficiências de remoção de fenóis de 70% para 94% com fósforo, porém não houve aumento da produção de biogás com a correção nutricional. As maiores produções de metano ocorreram no R1, e foram de 0,29 e 0,74 L CH4 (L d)-1 nos diferentes ensaios. Adicionalmente, o sistema anaeróbio - aeróbio removeu de 40% a 71% de nitrogênio total Kjeldahl (NTK) e fósforo total (PT) sem correção nutricional do afluente, e 41% e 81% de NTK e PT quando o afluente foi corrigido. Houve remoções de elementos inorgânicos como Fe, Zn, Cu, Mn, Mg, Ca e K, principalmente durante a digestão anaeróbia. Observou-se baixo desempenho para a produção de biogás e qualidade do efluente no R2, embora permitisse estabilizar os choques de carga e compostos tóxicos, como fenóis, durante as mudanças nas características físico-químicas das ARC. No RBS ocorreram fenômenos de nitrificação e remoção...
Keywords: Café; Reatores UASB; Residuos agricolas; Resíduos industriais; Agua - Reutilização; Águas residuais - Purificação; Waste products